Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1128/jcm.00195-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Hospital-Acquired Vancomycin-Resistant Enterococci

Abstract: Vancomycin-resistant Enterococcus faecium strains are a significant cause of nosocomial infections in predisposed patients. Multiple-locus variable-number tandem repeat analysis (MLVA) has been validated recently by use of a global strain collection. In this report, we applied MLVA together with multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE) to type 14 isolates from three clusters of patients colonized or infected with vancomycin-resistant Enterococcus faecium and another 10 epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
1
21
2
2
Order By: Relevance
“…CC17 is the only recognized E. faecium HiRCC, nowadays globally disseminated, which has been sporadically isolated from nonhospitalized humans (3,(8)(9)(10). Different studies have analyzed the population structure of local enterococci, but they are focused mainly on clinical strains with a specific phenotype, such as vancomycin resistance, generally isolated in a short temporal frame (2,7,16,18,27,29,36).…”
mentioning
confidence: 99%
“…CC17 is the only recognized E. faecium HiRCC, nowadays globally disseminated, which has been sporadically isolated from nonhospitalized humans (3,(8)(9)(10). Different studies have analyzed the population structure of local enterococci, but they are focused mainly on clinical strains with a specific phenotype, such as vancomycin resistance, generally isolated in a short temporal frame (2,7,16,18,27,29,36).…”
mentioning
confidence: 99%
“…It has been suggested that the CC5 lineage of E. faecium may have a fitness advantage in swine and could spread more readily than other, less adapted strains between swine and potentially between swine and humans (47). Many studies have shown that it is possible for the same strains of enterococci to infect both humans and farm animals (3,6,13,23,33,53,56). If large numbers of CC5 strains acquire vancomycin resistance, this could pose a health threat to humans since this also suggests the potential for the occurrence of vancomycin-resistant enterococci in food.…”
Section: Discussionmentioning
confidence: 99%
“…This has been attributed to less use of vancomycin and extended-spectrum cephalosporins in European hospitals (35). Recently, there have been reports of increasing numbers of infections with VRE in hospitalized patients in European countries (3,21,34,37,46,64). A specific clonal complex of E. faecium strains, clonal complex 17 (CC17), has been responsible for outbreaks in hospitals worldwide, including the United States (7,38,39,45,64).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of VRE ranges from 20 to 40 % in the USA and is .10 % in some European countries (Abele-Horn et al, 2006). Since the use of the glycopeptide antibiotic avoparcin (a vancomycin analogue) as a growth promoter in animals, VRE has also been demonstrated in the faeces of avoparcin-exposed farm animals and animal-derived food products such as raw meat.…”
Section: Introductionmentioning
confidence: 99%